Competition and complementarity of retailing in the historic city centre of Vienna - Gerhard Hatz (Belgeo)
The purpose of this study is to explore the effects of competition and complementarity on retailing in the historic city centre of Vienna and to analyse the changes brought about by these mechanisms. This concerns the status of Vienna’s city centre as a prime shopping location and the way this position has been undergoing significant changes. But it also concerns the structures and spatial organisation of retail in this main shopping district. The study itself is based on a survey of a sample of about 2000 shops.Three indicators serve as a basis to analyse the effects competition and complementarity have exerted on the retail premises: retail sectors, chain operation and store sizes. On a spatial level, the analysis is based on the functional units that constitute the historic city centre of Vienna.In the historic city centre of Vienna fierce competition among retailers is bringing about a reduction of the number of competitors but not a decrease in the number of retail premises. Nationally and internationally operating chains are the ‘driving forces’ of restructuring retailing and its related spatial patterns. Other retailers are forced to find free niches or market segments, which are defined by the principle of complementarity to retail sectors, retail forms or locations of national or international chain stores. The study comes to the conclusion that the effects of competition and complementarity cannot be explained in their totality, but they have to be interpreted as to the impact they have on the spatial organisation of the city. The competition between large-scale multinational chains is the source of the dynamic process that keeps transforming the entire retail trade in downtown Vienna. This process is regarded as crucial for the vitality of retailing in the city centre, as supplementary retail structures in surrounding neighbourhoods are provided with new opportunities and niches. The dynamics triggered by multinationally operated chain stores, are mutually related to the emergence of highly specialized supplementary zones adjacent to the main shopping streets. The larger retail formats in the main shopping area vice versa benefit from the specialised supplementary zones, which respectively contribute to maintaining the high standards of the Main Shopping Area but also to supporting the city as a prime shopping location, even though the observed restructuring of retail is converting the historic city centre into a themed destination for leisure shopping.